Edukasi Kesehatan Reproduksi Dan Pencegahan HIV/AIDS Melalui Metode Pendidikan Sebaya Bagi Remaja Perempuan Di Medan Johor - Humaida Hanim; Khairunnisa Situmorang; Citra Oktavia Nainggolan; Nur Ainun Boru Sitepu (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Adolescent girls face various challenges in understanding reproductive health and the risks of sexually transmitted infections (STIs), including HIV/AIDS. Limited education and communication barriers with parents lead many adolescents to seek information from unreliable sources. This community service program aimed to enhance adolescent girls' understanding of reproductive health and HIV/AIDS prevention through the peer education method. The program was conducted in Karya Tani, Kecamatan Medan Johor, Pangkalan Masyhur, involving 18 adolescent girls aged 15-19 years as the primary participants. The methods used in this program included Focus Group Discussions (FGD), refusal skills training, interactive discussions, and pre-test and post-test evaluations. The evaluation results indicated a 5% increase in knowledge about reproductive health, a 10% improvement in HIV/AIDS awareness, and a 39% rise in participants’ self-confidence. Although the program had a positive impact on increasing adolescent awareness, challenges remained, such as limited program duration, low parental involvement, and communication barriers in discussing reproductive health issues. As a recommendation, extending the program duration, actively involving parents and educators, and collaborating with local health institutions are essential to ensure sustainable education. This program is expected to serve as a model for improving adolescent girls' understanding of reproductive health and HIV/AIDS, enabling them to make more informed decisions regarding their health and future.